Difference between Auditory and Visual Students on Their Writing Achievement - Nurani, Salsabila Gita (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Students’ learning styles is related to their study achievement, but what exactly the appropriate style that can influence their achievement deeply is one of the questions in recent day. This research was conducted in order to know whether there is a difference between auditory and visual learners especially in their writing achievement as the researchers argued that writing English is the most complicated skill than other English skills. Quantitative design was used in this research and the participants were selected randomly from male and female students in University of Islam Malang. They were students of English Department in fourth semester. The study found that there is no significant difference between auditory and visual students in their writing achievement. The suggestion for the next research is to consider including another learning style such as kinesthetic learners.